ALOn BKI: Developing Digital Innovation for Islamic Counseling Services - Rosyidi, Fajar; Ahmad Nafi (Universitas Islam Negeri Madura, 2025)
This study aims to develop an online Islamic Counseling Guidance (ALOn BKI) service application as an innovative solution to expand access to digital technology-based Islamic counseling. This application is designed using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model approach, which provides a systematic framework in each stage of development. The focus of the study includes user needs analysis, application design and development, implementation, and effectiveness evaluation. The results of the study indicate that ALOn BKI has succeeded in providing flexible and practical Islamic counseling services, equipped with interactive features such as chat, video calls, and materials based on sharia values. The application trial showed a high level of user satisfaction, especially in terms of ease of access and relevance of services to Islamic teachings. In addition, the reminder and ongoing guidance features support the counseling process effectively. However, there are challenges in the form of low digital literacy in some users and the need to strengthen the personal data security system. Recommendations for further development include the addition of analytical features to track client progress and thematic support groups. In conclusion, ALOn BKI makes a significant contribution to increasing the accessibility and effectiveness of technology-based Islamic counseling services. This application has the potential to be a model for the development of religion-based counseling services in the future